Long Distance Learning, Challenges And Opportunities - Vera Sri Wahyuni; Dian Wulandari; Soewarto Hardhienata (STAI Miftahul Ula Nganjuk, 2021)
The spread of the Covid-19 pandemic has caused disruption to Indonesia's education sector where approximately 45 million students are unable to continue their learning activities in school. One solution is Long Distance Learning, this study aims to find out (1) the long distance remote learning system applied, (2) the impact of the Long Distance Learning system on student achievement, (3) obstacles in the application of Long Distance Learning system. The research method used in this study is qualitative method with descriptive research type qualitative approach. The results of this study show that the implementation of Long Distance Learning still has many obstacles such as inadequate equipment and poor internet connection, in addition to the increase in learning success is still small and ineffective